2018
DOI: 10.22146/ijeis.35817
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Support Vector Machine to Preterm Birth Prediction

Abstract: Preterm birth is one of the major contributors to perinatal and neonatal mortality. This issue became important in health research area especially human reproduction both in developed and developing country. In 2015 Indonesia rank fifth as the country with the highest number of premature babies in the world. The ability to reduce the number of preterm birth is to reduce risk factors associated with it. This research will be made the prediction model of preterm birth using hybrid multivariate adaptive regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The function's basis explains the relationship between the response variable and the predictor. It was suggested that the maximum number of basic functions (BF) is two to four times the number of predictor variables while the maximum number of interactions (MI) is one, two, or three, knowing that more than three results in a very complex model and a minimal distance between knots or minimum observation (MO) of zero, one, two, three, five, and ten [31]. Multivariate Adaptive Regression Spline (MARS) is a non-parametric function that is a complex combination between spline regression and recursive partitioning (RPR) [32].…”
Section: Conceptual Of Multivariate Adaptive Regression Spline (Mars)mentioning
confidence: 99%
“…The function's basis explains the relationship between the response variable and the predictor. It was suggested that the maximum number of basic functions (BF) is two to four times the number of predictor variables while the maximum number of interactions (MI) is one, two, or three, knowing that more than three results in a very complex model and a minimal distance between knots or minimum observation (MO) of zero, one, two, three, five, and ten [31]. Multivariate Adaptive Regression Spline (MARS) is a non-parametric function that is a complex combination between spline regression and recursive partitioning (RPR) [32].…”
Section: Conceptual Of Multivariate Adaptive Regression Spline (Mars)mentioning
confidence: 99%
“…Machine learning has been previously applied to PTB prediction or PTB stratification through many different techniques, such as SVMs 8 , neural networks [9][10][11] and decision trees 12,13 . However, the most commonly used ones are logistic regression and linear regression, employed in the analysis and prediction using many distinct SES facets: poverty 14 , pregnant mother's working conditions 15,16 , general social factors 17,18 and clinical and hereditary factors [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Várias técnicas de aprendizagem de máquina foram previamente aplicadas ao problema para predic ¸ão ou estratificac ¸ão do risco PTB, incluindo SVMs [8], redes neurais [9]- [11] e árvores de decisão [12], [13]. No entanto, as aplicac ¸ões mais comuns são as técnicas de regressão logística e de regressão linear, empregadas na análise e na predic ¸ão de PTB para diferentes fatores: a pobreza [14], as condic ¸ões de trabalho da gestante [15], [16], fatores sociais em geral [17], [18] e, principalmente, fatores clínicos ou hereditários [19]- [22].…”
Section: Introduc ¸ãOunclassified